The Role of Quranic Education Centers in the Formation of Noble Character (Akhlaqul Karimah) Among Students - Sari, Novi Indah; Mufidah, Luluk Indarinul; Sari, Galuh Kartika (IERA, Islamic Education and Research Academy, 2023)
The objective of this research is to: (1) Identify the methods employed in developing akhlaqul karimah among students at Assa’adah Juwet. (2) Explore the efforts made by educators in fostering akhlaqul karimah among the students. (3) Analyze the factors that support and hinder the implementation of akhlaqul karimah development at Assa’adah Juwet. The research employs a descriptive qualitative methodology, which includes direct observations of the research subjects, interviews with experts, and consultations with valid sources, followed by direct observation to conclude based on the findings. The results of the study conducted at TPA Assa’adah Juwet reveal that the implementation of akhlaqul karimah among students is generally positive, as most students have successfully incorporated akhlaqul karimah in their activities both at the learning center and in their daily lives. However, there is still a need for further enhancements to achieve optimal outcomes.